Local Wisdom as Halal Tourism Model in West Sumatera: an `Urf Perspective - darlis, rusyaida (Indonesian Journal of Islam and Muslim Societies, 2025)
The purpose of this research is to explore the uniqueness of halal tourism in West Sumatra, including the development of such locally wise-based halal tourism, its harmony with `urf principles, and its advantages and disadvantages. By employing a qualitative research method, this research applies a case study approach to analyse halal tourism destinations in the region. The results of this research indicated that the uniqueness of halal tourism in the province of West Sumatra is attributable to the highly-coherent integration of religion and customs. This is reflected by the use of “gonjong,” a horn-like curved roof, in most of the mosques in the region; the wearing of "baju basiba," a traditional attire according to Islamic syariah guidance, by local women in traditional events; the tradition of “makan bajamba” feast, a communal dining to preserve manners and refined etiquette among the people; and the existence of traditional tourism villages with their historic and unique buildings. The evolving local wisdom forms a distinctive `urf that has become a living norm within the community and has developed into local regulations or laws